2020
DOI: 10.1371/journal.pone.0238069
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practice of post exposure prophylaxis for HIV among nurses at Jigme Dorji Wanghuck National Referral Hospital, Bhutan

Abstract: Nurses are managing huge number of patients infected with human immunodeficiency virus (HIV), which made them highly vulnerable to HIV infection through occupational exposure such as needle stick injuries and splashing of blood/bodily fluids on mucosal surface. This made the practice of post exposure prophylaxis (PEP) for HIV crucial among nurses. Therefore, our study aimed to assess knowledge, attitude and practice of PEP for HIV among nurses in Bhutan. A cross-sectional study was conducted among 221 register… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
3
9
1
Order By: Relevance
“…According to this systematic review and meta‐analysis, the estimated pooled uptake of HIV/AIDS PEP among healthcare providers in Africa with a random‐effects model was 40.09% (95% CI: 30.14–50.04). This study is similar with study conducted in Pakistan (35.3%) [62,64], but higher than studies conducted in Bhutan (2.1%) [63] and Portugal (1.8%) [64]. This might be due to variations in sociodemographic characteristics, knowledge level and accessibility of the drug.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to this systematic review and meta‐analysis, the estimated pooled uptake of HIV/AIDS PEP among healthcare providers in Africa with a random‐effects model was 40.09% (95% CI: 30.14–50.04). This study is similar with study conducted in Pakistan (35.3%) [62,64], but higher than studies conducted in Bhutan (2.1%) [63] and Portugal (1.8%) [64]. This might be due to variations in sociodemographic characteristics, knowledge level and accessibility of the drug.…”
Section: Discussionsupporting
confidence: 88%
“…Funnel plot with pseudo 95% confidence limits F I G U R E 8 Sensitivity analysis of pooled prevalence of knowledge for each study being removed one at a time similar with study in Pakistan (35.3%) [62,64], but higher than studies conducted in Bhutan (2.1%) [63] and Portugal (1.8%) [64]. This might be due to variations in sociodemographic characteristics, knowledge level and accessibility of the drug.…”
Section: Log Plvmentioning
confidence: 99%
“…Regarding immediate measures taken after exposure, half of the respondents in the current study reported that they washed the exposed area with water and soap and one-fourth washed the exposed area with alcohol and iodine, whereas a study conducted in Debre Markos revealed that 68.6% of respondents washed the wound with soap and water and 14.9% squeezed and washed with alcohol. 7 In the present study, almost one-tenth of the study participants did not use PEP, which is lower when compared with a study conducted in Botswana (74.8%), 10 a study in Bhutan (97.9%) 15 and a study from Debre Markos town (56.7%). 7 This might be due to differences in the number of those individuals who were exposed and in general due to the difference in the number of the study participants and the difference in the percentile calculation…”
Section: Discussioncontrasting
confidence: 60%
“…12 In the current study, less than half of the respondents had poor knowledge, which is slightly higher than a study conducted among HCWs in public health institutions in Debre Markos town (36.1%), 7 a study conducted in Gondor, northwest Ethiopia (36.9%) 13 and a study conducted in Hiwot Fana Specialized University Hospital in Harar (17%), 14 but much lower than the study conducted in Nigeria (57%) 6 and a study conducted at Jigme Dorji Wangchuck National Referral Hospital, Bhutan (80.1%). 15 This could be due to the difference in the knowledge assessment like the availability of PEP service and training in this survey and also a difference in the study setting and the difference in health professionals involved in the study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation